Temperature dependence of electron density and electron–electron interactions in monolayer epitaxial graphene grown on SiC. (25th January 2017) - Liu, Chieh-Wen; Chuang, Chiashain; Yang, Yanfei; Elmquist, Randolph E; Ho, Yi-Ju; Lee, Hsin-Yen; Liang, Chi-Te
Abstract: We report carrier density measurements and electron–electron ( e – e ) interactions in monolayer epitaxial graphene grown on SiC. The temperature ( T )-independent carrier density determined from the Shubnikov–de Haas (SdH) oscillations clearly demonstrates that the observed logarithmic temperature dependence of the Hall slope in our system must be due to e – e interactions. Since the electron density determined from conventional SdH measurements does not depend on e – e interactions based on Kohn's theorem, SdH experiments appear to be more reliable compared with the classical Hall effect when one studies the T dependence of the carrier density in the low T regime. On the other hand, the logarithmic T dependence of the Hall slope δR xy / δB can be used to probe e – e interactions even when the conventional conductivity method is not applicable due to strong electron–phonon scattering.